Botanic analysis of Livia's villa painted flora (Prima Porta, Roma) (JOURNAL OF CULTURAL HERITAGE, 2003)
The frescoes of Livia's villa at Prima Porta, Rome, are the most famous representations of Roman gardens. The painted flora is analyzed from the scientific viewpoint and previous identifications are critically discussed. Here, 24 different species are described, giving information on the taxonomic, and phytogeographic position. Most of them belong to the spontaneous elements present in the Mediterranean forests, maquis and grasses of Southern Italy, such as Arbutus unedo, Laurus nobilis, Nerium oleander, Quercus ilex, Quercus robur gr., Comas mas, Myrtus communis, Phyllitis scolopendrium, Viola reichenbachiana, Chrysanthemum coronarium, Anthemis cotula, or widely cultivated, such as Cupressus sempervirens. cydonia oblonga, Pinus pinea, Punica granatum, Papaver somniferum, Rosa centifolia, Phoenix dactylifera. A symbolistic purpose of the pictures is also clearly evident. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.